STUDI AKSESIBILITAS DAN KUALITAS APLIKASI KORTIKO.EDU PADA ORANG TUA DENGAN ANAK CEREBRAL PALSY DI KOMUNITAS HAPPY CP FAMILY SURABAYA - Khabib Abdullah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Cerebral palsy (CP) is a disorder of movement and function due to permanent damage to brain cells during growth and development. One of the interventions that can be given is to do exercise therapy by a physiotherapist. However, 20 parents with CP children in the happy CP family Surabaya community had difficulty getting access to physiotherapy services in Surabaya, so the kortiko.edu application was created to provide education in the form of exercise therapy videos for CP children for these parents. Until now, the level of ease of access, clarity of images and sound and clarity of narration in video applications has not been known.Methods: 20 parents in the happy CP family community who have limited access to physiotherapy services participated in this study. The research began by conducting video calls between parents and child physiotherapists to carry out virtual assessments and examinations. Then select a number of videos on the kortiko.edu application that are suitable for learning and imitating the movements. Then parents were asked to rate the quality of the application in terms of ease of access and audio-visual quality by filling out a questionnaire.Results: out of 20 respondents stated that 100% was easy to download the application, 90% was easy to use the application, 65% stated that the sound of the video was clear, 50% stated that the video image was clear, 35% stated that the video explanation was easy to understand, and 60% stated that the movements in the video were easy done. Some parents suggest increasing the duration of the video and making videos with real CP children as subjects.Conclusion:Â the kortiko.edu application is very easy to access and use, but the quality of the application needs to be improved in terms of video duration and involving CP children as video models.